When do prevocational programs ease the transition to vocational education and training? - Robin Busse; Elisabeth Maué (Vocations and Learning, 2025)
Preparing youth for the transition from school to work is a key labor market challenge in many countries. Across Europe, there are many educational pograms to improve youth's school-to-work transitions. In Germany, youth with difficulties in their school-to-work transitions are channeled into prevocational programs to help them to enter vocational education and training (VET), which serve as an entry into the labor market. Using data drawn from the National Educational Panel Study (NEPS; N 0.167em=0.167em1,282 participants of prevocational programs), we (1) examined youth's transition trajectories after their attendance of a first prevocational program and (2) how using institutional resources such as internships during the first prevocational program supports youth's transitions to VET. Our findings of sequence and cluster analysis showed that approximately two-thirds of the participants had largely stable transitions to VET (i.e., transitions with a low risk of dropout), although many of these transitions were delayed by one year after leaving their first prevocational program. In contrast, one-third of the participants had at-risk transition trajectories and were at risk of being permanently excluded from the education and employment system. By conducting a multinomial logistic regression, we also found that attending long internships and attaining a higher school certificate during the first prevocational program was associated with a smooth transition to VET programs, and both factors “protected” youth from encountering difficult pathways with very low prospects of reaching VET programs after leaving prevocational programs. Moreover, mentoring during prevocational programs and the perceived degree to which the programs helped youth to form occupational aspirations were also associated with a lower probability of facing at-risk transition trajectories.
Keywords: 370; School-to-work transition; Transition sector; Prevocational programs; Vocational orientation; Mentoring; Internships; School certificates